Primitivism, Radicalism, and the Lamb's War : the Baptist-Quaker Conflict in Seventeenth-Century England. - Underwood, Ted LeRoy (Oxford studies in historical theology., 1997)
The mid-17th century saw both the expansion of the Baptist sect and the rise of Quakerism. At first, the Quaker movement attracted some Baptist converts, but relations between the two groups soon grew hostile. However, this book contends that Quakers and Baptists had much in common with each other.